On generalized K-Fibonacci sequence by two-cross-two matrix - Wani, Arfat Ahmad; Rathore, G. P. S.; Sisodiya, Kiran (Global Journal of Mathematical Analysis, 2016)
In this study we define a new generalized k-Fibonacci sequence associated with its two cross two matrix called generating matrix. After use the matrix representation we find many interesting properties such as nth power of the matrix, Cassini's Identity of generalized k-Fibonacci sequence as well as Binet's formula for generalized k-Fibonacci sequence by the method of matrix diagonalization.